PENGEMBANGAN LEMBAR KERJA SISWA (LKS) BERBASIS CONTEXTUAL TEACHING AND LEARNING (CTL) PADA MATERI FAKTORISASI SUKU ALJABAR KELAS VIII SMP NEGERI 9 MUARO JAMBI - Apriani Apriani; Buyung Buyung; Relawati Relawati (Universitas Batanghari Jambi, 2017)
This study aims to develop LKS contextualizing algebra-based factorization subjects based on Contextual Teaching and Learning (CTL) for grade VIII SMP students and to know the quality of LKS from the aspect of validity and practicality based on the assessment of material experts, design experts, media experts, student assessment on individual trials , student ratings on small group trials, and student ratings on field trials. Validation is done by 2 material experts, design experts, and media experts. The developed LKS were tested in 3 stages, one to one leaner stage with 3 subjects, small group try-out stage with 6 subjects, and field trials (field try-out) with the subject of 23 students. The result of the research shows that the quality of Student Worksheet (LKS) mathematics of algebra based factorization material based on Contextual Teaching and Learning (CTL) based on the assessment: 1) the material experts obtained the average total of 3.81 included in the